POSITIVE CHANGES AND INACCURACIES IN THE UKRAINIAN 2019 SPELLING - Kateryna S. Bondarchuk; Olha A. Chumachenko (Вісник університету ім. А. Нобеля. Серія Філологічні науки)
The aim of the article is to analyze Ukrainian spelling peculiarities, highlighted in the editions of 1993, 2007 (amended version) and 2019 years, which are related to the comparative aspect, particularly to orthography (methods of combining sounds and sound combinations which ensures the same type of words’ spelling). The work uses such approaches as induction and deduction, and the main methods of researching linguistic phenomena: descriptive method and variant dynamics of writing foreign words. In the study, using the application of comparative and contrastive methods, we have determined some features of literary language norms in the spellings of 1993 and 2007, which relate to minor clarifications, descriptions, the illustrative material alphabetical order, the selection of certain lexemes to denote concepts related to changes in society, and some modernized changes in spelling. It is proved that corrections were made to the spelling of 2007 not in relation to Ukrainian grammar and orthography but mainly in relation to illustrative material, and these examples sometimes do not correspond to literary language norms. The article analyzes some positive changes regarding to various subsystems, which truly corresponds to the Ukrainian language modern state, for instance, normalized spelling of borrowed words such as “top100” or “top-ten”, names of sites and other Internet services, and complex words with borrowed components (vice-, ex-, leib-, maxi-, midi-, mini-, ober-, unter-, stubs-, which now we write together). The spelling of such words like “проєкт” and “проєкція”, the principle of transmission of Russian and Belarusian names and some male surnames in the adjective form, the spelling of the pronouns “ви” and “ваш” with lowercase and uppercase letters have been standardized. It has been proven that there are no significant changes in 2019 Spelling: the vast majority of them are contradictory and even not entirely appropriate. Especially, this alternation concerns of “о - і” and “е - і” with verbose definitions that are too difficult for a schoolchild; some norms about the position of using prepositions and prefixes “у - в”, as well as prepositions “із, зі”. We have recorded some overcomplicated explanations regarding the lengthening of consonants, the use of a soft sign “ь”, etc. Innovations in the writing of foreign words have been studied in detail. Some of the new norms are clearly motivated, but some of them are too complicated, for example, the transfer of borrowed personal names including Arabic, Persian, Turkic and others. Irregularities in the spelling of various parts of the language have been identified, in particular regarding the features of the case endings of masculine nouns of the second declension of the singular; declension of Russian surnames with the suffixes “-ин, -ін, -їн” (parallel endings in the dative case form; use of a number of Russian surnames in the vocative case form). The authors moved the irregularity of some features quantitative and fractional numerals declension and their combination with nouns. The article contains authors’ critical comments regarding the clarity and accuracy of certain spelling norms formulation, for example, phonetic processes, the use of a soft sign “ь”, writing complex words, etc. Nouns declension peculiarities are analyzed, in particular those that determine the specificity of the Ukrainian language, its uniqueness. The proposed authors’ vision of formulations concretization about the quantitative and fractional numerals declension and their combination with nouns. In general, both positive changes in spelling norms and certain inaccuracies should be eliminated and refined.